The study of physico-chemical characteristics of power plant effluents at Basrah governorate. - Eassa, Amal M. (Al-Qadisiyah Journal of Pure Science, 2017)
The present study was conducted on Najibia and Hartha power plants to assess the physico-chemical characteristics of power plant effluents and to investigate the environmental impact resulting from them. The water samples from both power plants were collected for four weeks during Summer season in 2012 where water samples were taken from three sites (Inlet water, outlet cooling and outlet Industrial water) for analyzing seven parameters (water temperature, pH, electrical conductivity, total suspended solids, chloride, total phosphorus and total iron). Water temperature increased at site 2 (outlet cooling water) comparable with site 1 (inlet water) at Najibia and Hartha power plants, at Najibia power plant it exceeded Iraqi guideline value of waste effluents (Ë‚ 35 â—¦C) while at Hartha one it was within that guideline. pH values of the sampling sites at both power plants were found to be neutral to alkaline in nature, pH value of site 1 was within the Iraqi guideline value of surface water (6.5-8.5) and the effluents of both site 2 (outlet cooling water) and 3 (outlet industrial water) were within the Iraqi guideline value (6-9.5) of waste effluents which had no effect upon aquatic organisms. Electrical conductivity elevated at site 2 at Najibia power plant due to high temperature while at Hartha power plant, water electrical conductivity of site 2 was lower than that of site 1, the electrical conductivity result of site 3 at Najibia power plant was higher than that of site 1, and at Hartha power plant 2 it was lower than that of site 1. The highest average of suspended solids was at site 3 in Najibia power plant comparable with other sites while at Hartha power plant the least average of suspended solids was at site 3 comparable with the other sites. However, the effluents of both site 2 and 3 at both power plants did not exceed Iraqi guideline value (60 mg / l) of waste effluents. The average values of chloride ion for site 1 and 2 at both power plants were less than 1000 mg/l and this indicated that river water was suitable for cooling purpose while the average chloride’s ion values of site 3 at both power plants were within the Iraqi guideline value (600 mg/l) of waste effluents where they did not threaten the life of aquatic organisms. The prevalence of phosphorus compounds in industrial wastes referred to water treatment processes and the results of all sampling sites at both power plants were very high to produce eutrophiction phenomenon where it occurs in an aquatic environment when concentration of orthophosphorus is only 0.005 to 0.05 mg/l .The average values of total iron at site 1 did not exceed the guideline value (1 mg/l) of U.S. Environmental Protection Agency (1986) for freshwater aquatic life. Where as the concentrations of total iron in site 2 and site 3 at both power plants were within the Iraqi guideline value of waste effluents (2 mg/l).